Lithium toxicity: a case report - Paudel, Ujjawal; Bham, Gajendra; Bhatt, Prashant Raj; Ghimire, Pradeep; Parajuli, Aastha; Upreti, Dipesh (Journal of Patan Academy of Health Sciences, 2023)
Lithium is a commonly used drug for bipolar disorders and requires therapeutic dose monitoring due to its narrow therapeutic index. Acute lithium toxicity frequently occurs due to intentional intake of an excessive amount or due to its interaction with various medicines and medical conditions which alter its absorption or excretion. It may present primarily with neurological and gastrointestinal symptoms. We report a case of lithium toxicity in a patient with bipolar disorder probably due to dehydration and decreased intake of food and fluids. Frequent monitoring of serum lithium level while maintaining hydration and electrolyte balance successfully treated the lithium toxicity.